Virtues and Challenges of Integrating Quizziz App for English Learning in Remote Learning Context - Eka Wulandari (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
The pandemic situation for the last two years has brought an abrupt change in our education system. Face-to-face learning at schools must be changed into a hybrid learning setting, where it combines direct teaching and learning processes with an online learning system. Teachers and students must adapt to the situation and problems related to this new situation start to occur. Ways to minimize the problems must be considered to be able to get the maximum result from the hybrid learning process. Based on the literature study conducted in this research, it has been proven that the Quizziz app can be one of the best alternatives for English hybrid learning.  This application provides attractive, interactive, and fun media for online learning especially the English subject, which makes it suitable be considered one of the best options in this emergency remote learning situation. Besides, the nature of this application is also suitable for the nature of today’s generation. This paper describes in detail why Quizziz are one of the best options to use in English online learning and how to get the most from them as well minimizing their disadvantages.